Evaluation of the water quality of the microcuenca of the Chibunga-Ecuador river in seasonal variations, period 2013-2017 - Veloz Mayorga, Nancy Cecilia (2018)
The contamination variables that affect the water quality of the Chibunga River microbasin were evaluated by applying the community of criteria, accepted and defined for the research. The calculation of the Water Quality Index was made with the following variables: pH, dissolved oxygen, lead, cadmium, BOD5, fecal coliforms, phosphates, nitrates, total suspended solids, oils and fats and tensoactives monitored in ten points, four campaigns, and in dry and rainy season. Pollution factors whose quality is most affected in the dry season are dissolved oxygen and lead with poor quality, and in suspended periods suspended solids; The quality of fecal coliforms in all seasons and seasons monitored is terrible. The average water quality index for the microbasin in the period 2013 to 2017 is 58, indicating a REGULAR or little polluted state of it, it can be considered acceptable but not recommended for recreation, acceptable for agricultural production, livestock use and production fish farming, and not suitable for normal industry use without prior treatment.